Estimation of strength of glulam beams depending on defects of layers/Medinių klijuotų lenkiamųjų elementų stiprumo vertinimas pagal sluoksnių defektus - Baltrušaitis, Algirdas (Journal of Civil Engineering and Management, 1999)
Timber, as structural material, has various defects, especially knots. They influence the strength of timber members. The influence of knots is lower for glulam members when comparing with solid wood. The article is the theoretical and experimental investigation of influence of knots on the strength of glulam beams. Theoretical investigation deals with probability of coinciding of knots in the same cross-section of member. The factors of influence of knots on glulam beam strength are the results of theoretical investigations. The short-term tests on 12 model beams with measurements 2140×120×152 (h) mm were carried out in a testing machine. Results of these tests are in line with the conclusions of theoretical investigations and show the higher strength of glulam beams when comparing with solid members of the same quality. The long-term tests were carried out on model beams when temperature and moisture were cyclically changed. Wetting cycle – 14 days long, drying cycle – 7 days. Two series, 12 model beams each, were tested. The moisture of outer layer 20 mm depth changed from 6–8% to 20–22%, while the moisture in the rest area changed from 9% to 13%. The load of the first group of beams was 40% of short-term strength, and duration of tests 147 days. For the second group the normal stresses were σ = 18.2 MPa for each beam, and the duration of tests – 210 days. Deflection of beams was observed and moments of beams rupture were registered. The relationships between long-term strength and logarithm of time to failure for two types of model beams were the results of long-term tests. Long-term tests show the dependence upon the size of knots and long-term strength of glulam beams.Article in Lithuanian.First Published Online: 26 Jul 2012